Respuesta :
First confirm that [tex]y_1=xe^{-x}[/tex] is a solution to the ODE,
[tex]y''+2y'+y=0[/tex]
We have
[tex]{y_1}'=e^{-x}-xe^{-x}=(1-x)e^{-x}[/tex]
[tex]{y_1}''=-e^{-x}-(1-x)e^{-x}=(-2+x)e^{-x}[/tex]
Substituting into the ODE gives
[tex](-2+x)e^{-x}+2(1-x)e^{-x}+xe^{-x}=0[/tex]
Suppose [tex]y_2(x)=v(x)y_1(x)[/tex] is another solution to this ODE. Then
[tex]{y_2}'=v'y_1+v{y_1}'[/tex]
[tex]{y_2}''=v''y_1+2v'{y_1}'+v{y_1}''[/tex]
and substituting these into the ODE yields
[tex](v''y_1+2v'{y_1}'+v{y_1}'')+2(v'y_1+v{y_1}')+vy_1=0[/tex]
[tex]xe^{-x}v''+2e^{-x}v'=0[/tex]
[tex]xv''+2v'=0[/tex]
Let [tex]w(x)=v'(x)[/tex]. Then the remaining ODE is linear in [tex]w[/tex]:
[tex]xw'+2w=0[/tex]
Multiply both sides by the integrating factor, [tex]x[/tex], and condense the left hand side as a derivative of a product:
[tex]x^2w'+2xw=(x^2w)'=0[/tex]
Integrate both sides with respect to [tex]x[/tex] and solve for [tex]w[/tex]:
[tex]x^2w=C_1\implies w=C_1x^{-2}[/tex]
Back-substitute and integrate both sides with respect to [tex]x[/tex] to solve for [tex]v[/tex]:
[tex]v'=C_1x^{-2}\implies v=-C_1x^{-1}+C_2[/tex]
Back-substitute again to solve for [tex]y_2[/tex]:
[tex]\dfrac{y_2}{y_1}=C_2-\dfrac{C_1}x[/tex]
[tex]\implies y_2=C_2xe^{-x}-C_1e^{-x}[/tex]
[tex]y_1[/tex] already captures the solution [tex]xe^{-x}[/tex], so the remaining one is
[tex]\boxed{y_2=e^{-x}}[/tex]
A differential equation shows the relationship between functions and their derivatives.
The equation of [tex]y_2(x)[/tex] is: [tex]y_2 = -e^{-x}[/tex]
The given parameters are:
[tex]y_2 = y_1(x) \int\frac{ e^{(\int -P(x)\ dx)} }{ y_1^2(x) }dx[/tex]
[tex]y" + 2y' + y = 0[/tex]
[tex]y_1 = xe^{-x}[/tex]
The general equation is:
[tex]y" + P(x) y' + Q(x)y = 0[/tex]
Compare the above equation to [tex]y" + 2y' + y = 0[/tex]
[tex]P(x) = 2[/tex]
Integrate:
[tex]\int\limits^x_0 P(x') dx'= \int\limits^x_0 2 dx'[/tex]
[tex]\int\limits^x_0 P(x') dx'= 2x|\limits^x_0[/tex]
[tex]\int\limits^x_0 P(x') dx'= 2[x - 0][/tex]
[tex]\int\limits^x_0 P(x') dx'= 2[x ][/tex]
[tex]\int\limits^x_0 P(x') dx'= 2x[/tex]
We have:
[tex]y_2 = y_1(x) \int\frac{ e^{(\int -P(x)\ dx)} }{ y_1^2(x) }dx[/tex]
The above equation becomes:
[tex]y_2 = y_1(x) \int\frac{e^{(\int -2 dx)} }{ y_1^2(x) }dx[/tex]
Substitute [tex]y_1 = xe^{-x}[/tex]
[tex]y_2 = xe^{-x} \int\frac{ e^{(\int -2 dx)} }{ (xe^{-x})^2 }dx[/tex]
Integrate
[tex]y_2 = xe^{-x} \int\frac{ e^{-2x}}{ (xe^{-x})^2 }dx[/tex]
Evaluate the exponents
[tex]y_2 = xe^{-x} \int\frac{ e^{-2x}}{ x^2e^{-2x} }dx[/tex]
Cancel out common factors
[tex]y_2 = xe^{-x} \int\frac{1}{ x^2 }dx[/tex]
Rewrite as:
[tex]y_2 = xe^{-x} \int x^{-2}dx[/tex]
Integrate
[tex]y_2 = xe^{-x} \times -\frac{1}{x} + c[/tex]
[tex]y_2 = -e^{-x} + c[/tex]
Set c to 0.
[tex]y_2 = -e^{-x} + 0[/tex]
[tex]y_2 = -e^{-x}[/tex]
Hence, the equation of [tex]y_2(x)[/tex] is:
[tex]y_2 = -e^{-x}[/tex]
Read more about differential equations at:
https://brainly.com/question/14620493